PENGARUH TINGKAT PENDIDIKAN TERHADAP KEPUTUSAN MENJADI NASABAH DI PT. BANK MUAMALAT INDONESIA, TBK., CABANG PEMBANTU SIBUHUAN - Batubara, Sarmiana (Institut Agama Islam Negeri Padangsidimpuan, 2017)
This study determine whether there is influence of education level to the decision to become a customer in PT. Bank Muamalat Indonesia,Tbk., Auxiliary Branch Sibuhuan and how big the influence are. The research is quantitative explainatory, data collected using a questionnaire with sample 32 people. From the research results show the influence of education level to the decision to become a customer in PT. Bank Muamalat Indonesia, Tbk., Sibuhuan Sub-branch is very positively influential. Great influence of education level to the decision to become a customer in PT. Bank Muamalat Indonesia, Tbk., Sibuhuan Sub-branch is using the product momant calculation, it turns out the correlation number between variable X and variable Y is not negative sign, meaning that between the two variables there is positive correlation (correlation that goes unidirectional). By considering the amount of rxy (ie = 0.155), whose magnitude ranges from 0.00-0.19 means between variables X and Y are very weak or very low correlation. Interpretation by using Table Value